2017
DOI: 10.1105/tpc.17.00313
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocally Retained Genes in the Angiosperm Lineage Show the Hallmarks of Dosage Balance Sensitivity

Abstract: In several organisms, particular functional categories of genes, such as regulatory and complex-forming genes, are preferentially retained after whole-genome multiplications but rarely duplicate through small-scale duplication, a pattern referred to as reciprocal retention. This peculiar duplication behavior is hypothesized to stem from constraints on the dosage balance between the genes concerned and their interaction context. However, the evidence for a relationship between reciprocal retention and dosage ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
93
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 122 publications
11
93
0
1
Order By: Relevance
“…We then tested 155 whether functionally related gene groups-gene ontologies (GO) or metabolic networks (Schlapfer et al 2017)-exhibited patterns of reciprocal retention. As previously observed (Freeling 2009;Coate et al 2016;Tasdighian et al 2017), we found that both GO terms and metabolic networks with high retention following WGD tended to have lower retention of SSD (linear regression for GO terms, slope = −0.6972, R 2 = 0.1839, F = 175.05 , df = 1 and 777, P < 0.001; linear regression for metabolic networks, slope = 0.6667, R 2 = 0.0886, F = 17.31, df = 1 and 178, P < 0.001 ; Fig. 1 a,b).…”
Section: Classes Of Genes Grouped By Gene Ontology and By Metabolic Nsupporting
confidence: 85%
See 3 more Smart Citations
“…We then tested 155 whether functionally related gene groups-gene ontologies (GO) or metabolic networks (Schlapfer et al 2017)-exhibited patterns of reciprocal retention. As previously observed (Freeling 2009;Coate et al 2016;Tasdighian et al 2017), we found that both GO terms and metabolic networks with high retention following WGD tended to have lower retention of SSD (linear regression for GO terms, slope = −0.6972, R 2 = 0.1839, F = 175.05 , df = 1 and 777, P < 0.001; linear regression for metabolic networks, slope = 0.6667, R 2 = 0.0886, F = 17.31, df = 1 and 178, P < 0.001 ; Fig. 1 a,b).…”
Section: Classes Of Genes Grouped By Gene Ontology and By Metabolic Nsupporting
confidence: 85%
“…Three main lines of evidence support the GBH (Tasdighian et al 2017;Freeling 2009;Hou et al 2018;Edger and Pires 2009): 1) signaling cascades, regulatory networks and protein complexes that are known to be disrupted by unbalanced changes in protein abundance tend to exhibit reciprocal 35 retention patterns; 2) reciprocally retained genes exhibit greater selective constraint on sequence evolution (lower Ka/Ks) and less divergence in expression patterns than non-reciprocally retained genes; and 3) reciprocally retained genes often exhibit deleterious phenotypes when over or under expressed-this latter piece of evidence often cited as the ultimate proof needed to demonstrate dosage sensitivity and confirm the GBH. However, demonstrating that a deleterious phenotype is 40 induced by over-or under-expressing a gene provides evidence for dosage sensitivity at the protein level, but it does not necessarily follow that there exists dosage sensitivity at the level of gene copy number.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Overall, gene families evolve through gene duplication and loss events. Duplications can be divided into two overall categories: whole-genome multiplications (WGM) and small-scale duplications (SSD), including segmental, tandem, and transposoninduced duplication events (Panchy et al, 2016;Tasdighian et al, 2017). Individual gene families evolve by either one of these processes.…”
Section: Introductionmentioning
confidence: 99%